(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
Industrial effluents discharged into the river poses a serious threat to our environment; the research examines the impact of some heavy metals of Kaduna refinery effluent into the Romi River. It asserts the nature of effluent released into the water body and also the impact of effluent on water quality. However the important water quality became relatively slowly as early human could only judge water quality through the physical senses of sight, taste and smell, now a days there is an increase of contamination of natural water bodies by industrial effluents in developing and densely populated countries like Nigeria, because rivers are major means of waste disposal and especially effluents from industries nearby. The data used in this research were generated from direct field measurement of pH, Conductivity, and Turbidity, heavy metal profiles (Chromium & Nickel) from Kaduna Refinery Effluent. The mean concentrations of the metals; chromium, iron, nickel, and zinc with the standard deviation were found to be: < 0.01 ± 0.1 mg/kg, and 0.06 ± 0.1 mg/kg. This study has shown that the mean concentration of chromium and Nickel found to be lower than the World Health Organization (WHO) acceptable limits while the concentration values of nickel 0.06 ± 0.1 mg/kg and iron 0.06 ± 0.1 mg/kg as found to be higher than the WHO, acceptable limits of the metals) obtained at the effluent points and this implicate the industry adjacent to the area as one of the sources of heavy metals in the river.